2019
DOI: 10.1021/acsami.9b19183
|View full text |Cite
|
Sign up to set email alerts
|

Ambient-Temperature Waterborne Polymer/rGO Nanocomposite Films: Effect of rGO Distribution on Electrical Conductivity

Abstract: Electrically conductive polymer/rGO (reduced graphene oxide) films based on styrene and n-butyl acrylate are prepared by a variety of aqueous latex based routes involving ambient temperature film formation. Techniques based on miniemulsion polymerization using GO as surfactant and "physical mixing" approaches (i.e., mixing an aqueous polymer latex with an aqueous GO dispersion) are employed, followed by heat treatment of the films to convert GO to rGO. The distribution of GO sheets and the electrical conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 50 publications
(96 reference statements)
7
69
0
Order By: Relevance
“…8,9 Such amphiphilic character has recently been exploited to synthesise colloidally stable polymer particles using GO as a sole surfactant in miniemulsion polymerisation. [9][10][11][12][13][14] Using miniemulsion polymerisation, we have previously shown that the surfactant ability of GO can be utilised to synthesise polymer/GO nanocomposites where polymer particles are decorated with GO sheets. 9,10 Based on this approach, decoration or localisation of GO sheets around polymer particles greatly overcomes the restacking affinity of GO sheets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Such amphiphilic character has recently been exploited to synthesise colloidally stable polymer particles using GO as a sole surfactant in miniemulsion polymerisation. [9][10][11][12][13][14] Using miniemulsion polymerisation, we have previously shown that the surfactant ability of GO can be utilised to synthesise polymer/GO nanocomposites where polymer particles are decorated with GO sheets. 9,10 Based on this approach, decoration or localisation of GO sheets around polymer particles greatly overcomes the restacking affinity of GO sheets.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Using miniemulsion polymerisation, we have previously shown that the surfactant ability of GO can be utilised to synthesise polymer/GO nanocomposites where polymer particles are decorated with GO sheets. 9,10 Based on this approach, decoration or localisation of GO sheets around polymer particles greatly overcomes the restacking affinity of GO sheets. This approach can be used to fabricate polymer/GO nanocomposite lms with controlled GO morphology mediated by the self-assembly of the GO sheets leading to their homogeneous distribution throughout the lm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1D; black curve). 32,[35][36][37][38] In reference to GO, the G band in AGO showed a marginal shi from 1604 to 1597 cm À1 , which may be due to the electrondonating nature of EDA in AGO or restoration of the sp 2 domain ( Fig. 1D; red curve).…”
Section: Characterization Of Go and Agomentioning
confidence: 97%
“…[26] We have successfully prepared nanoparticles "armored" with GO sheets via miniemulsion copolymerization of styrene and butyl acrylate using GO as sole surfactant, exploiting the amphiphilic properties of GO, followed by thermal reduction of GO to rGO. [29][30][31][32][33][34][35][36][37] The synthesis of polymer/rGO nanocomposites employing aromatic monomers such as styrene utilizing π-π interactions has been demonstrated. [26,31,[38][39][40] Preparation of polymer/rGO nanocomposites with other monomers such as acrylates, utilizing modification of rGO, has also been reported.…”
Section: Doi: 101002/marc202000141mentioning
confidence: 99%